A designed and potentially decadentate ligand for use in lanthanide(iii) catalysed biomass transformations: targeting diastereoselective trans-4, 5-diaminocyclopentenone derivatives. Issue 7 (5th February 2020) - Peewasan, Krisana; Merkel, Marcel P.; Fuhr, Olaf; Powell, Annie K.
Abstract : The catalysis of furfural to diastereoselective trans -4, 5-diaminocyclopentenone building blocks for natural product synthesis for a wide range of amines was achieved under mild aerobic conditions. Abstract : The goal of this study was to design a ligand system which can accommodate single lanthanide(iii )-ions and investigate the properties of the resulting complexes. The complexes of all the accesible lanthanides and yttrium with the new ligand LH6 = N, N ′-dimethyl- N, N ′-ethylene-bis(5-bromo-3-(1 H -benzimidazol-2-yl)hydrazineylidene)-2-hydroxybenzylamine) were obtained in high yield at room temperature under aerobic reaction conditions. The corresponding compounds were characterised using X-ray diffraction, FT-IR, elemental analysis and the optical properties of all complexes were investigated using UV-vis and fluorescence spectroscopy. The air stable complexes efficiently transform biomass furfural to trans -4, 5-cyclopentenones in high yield.